ANALYSIS OF TRANSLATION TECHNIQUES AND QUALITY OF TRANSLATED TERMS OF MECHANICAL ENGINEERING IN ACCREDITED NATIONAL JOURNALS - Mohammad Febryanto; Iis Sulyaningsih; Alliyah Anggarani Zhafirah (PROJECT (Professional Journal of English Education), 2021)
This study investigates the technique of translating mechanical engineering terms from Indonesian to English in accredited national journal abstracts and the quality of the translation results. Qualitative descriptive is used as a research method. The abstracts taken as data are from the national journals accredited in 2019 and 2020, consisting of 59 articles. In collecting data, document analysis is used as a tool to collect data. The results showed that adaptation techniques, common equivalent techniques, literal translation techniques, calque techniques, and pure borrowing techniques are techniques used in translating mechanical engineering terms, and the average value of the quality of the translation results is good. Keywords:  Translation Techniques, Translation Quality, Mechanical Engineering Terms